Social Responsibility in the Hospitals of the SR Health Network: Estructura y funcionamiento - Red Sanitaria de Responsabilidad Social, (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We present the results of a study that explores the management of social responsibility in thirteen hospitals of the RS Health Network. The findings reveal that these hospitals manage the SR professionally and with quality criteria, oriented to compliance with the SDGs, within the framework of the strategic plan of each hospital. Although, deficits are still detected in its departmental implementation, its planning, and the evaluation of its impacts. And some weaknesses such as lack of resources and leadership. To overcome them, the hospital’s management support is decisive. The RS Health Network is a model for collaboration.